การพัฒนานวัตกรรมหลักสูตรศิลปศึกษาบนฐานบริบทร่วมสมัย - สุชาติ ทองสิมา (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
The purposes of this research were 1) to study and determine the conceptual framework of art education curriculum and contemporary context; 2) to study characteristics of art education curriculum on the stakeholder demand; 3) to develop the innovative art education curriculum based on contemporary context. The research methodology was a mixed method divided in three phases. 1) The qualitative research was studying and researching documents and related research, then interviewing with 19 experts in art education and contemporary contexts. 2) The research was conducted by questionnaires with 803 stakeholders in the curriculum. 3) The research was also conducted by developing an innovative art education curriculum based on a contemporary context, and using the focus group technique with 12 experts in art education and contemporary contexts to assess the prototype of innovative curriculum. The qualitative data was analyzed by using thematic framework, coding/indexing, Interpreting and summarizing data reduction techniques. The quantitative data was analyzed by using percentage, means, standard deviation and Modified Priority Needs Index (PNImodified) statistics. The result of the first phase of the study indicated the conceptual framework of art education curriculum should consist of seven concepts: 1) Fundamental Theory Art Education; 2) Pedagogical Art Education; 3) Technology and Innovation Art Education; 4) Local and Wisdoms Art Education; 5) Entrepreneurship Art Education; 6) Personalized Art Education; 7) Transdisciplinary Art Education. The conceptual framework of contemporary context consists of 5 concepts: 1) Personalization 2) Transdisciplinary 3) Localization 4) Innovation 5) Finance and Entrepreneurship. The second phase of the study found that the highest desirable condition of 1) the teachers was the Fundamental Theory Art Education objective; 2) the graduates was the Pedagogical Art Education objective; 3) the graduate supervisors was the Fundamental Theory Art Education objective. The third phase of research revealed that the innovative art education curriculum based on contemporary context is 1) the curriculum structured as the Personalized Learning that requires elective major credits higher than compulsory major credits. It allows learners to choose to develop themselves according to their potential and interests 2) The curriculum content should integrate with music and dance education and the fields of humanities, social sciences and science.